Environmental Content as a Part of Science-Oriented Sustainable Development Goals in Grades 6 and 7 of Slovenian Primary School: An Analysis of Science Textbooks - Vošnjak, Matej; Rebolj, Neva; Devetak, Iztok (CEPS journal, 2024)
Slovenian science education in Grades 6 and 7 (11- and 12-year-old students) of primary school focuses on the integration of various science subjects. According to the current Slovenian science curriculum, environmental concepts, as a part of science-oriented sustainable development goals, are an integral part of the subject of science. In 2026, a new science curriculum will be introduced in the education system to provide students and teachers with competences for sustainable development. Consequently, the aim of this study is 1) to analyse old (valid prior to the 2010/2011 school year) and current 6th and 7th-grade Slovenian science curriculum for primary school from an environmental and sustainability perspective, and 2) to investigate textual and pictorial material of four 6th grade and four 7th grade textbooks available for students in the current school year (2023/24) of primary school, that relate to environmental content, as well as their overall structure. The analysis of the textbooks showed that all textbooks explain some environmental topics recommended by the national curriculum. The text is supported by pictorial elements that present phenomena with realistic pictures on the macrolevel. The present study suggests that some environmental content is present in 6th- and 7th-grade science textbooks that are consistent with the learning goals of the curriculum but that a significant amount of sustainability content is missing. For this reason, the curriculum reform currently underway in Slovenia should more clearly include the implementation and thoroughly consider the integration of science-oriented sustainable development goals into the science curriculum in Grades 6 and 7.